Análise de desempenho de linhas de transmissão frente a descargas atmosféricas: estudo comparativo de alternativas para melhoria de desempenho de LTs de 230 e 500 kv - Ana Paula Gomes Grabe Borges (2024)
The performance of transmission lines (TLs) is directly related to the number of non-scheduled outages that occur in a TL per year, with lightning strikes being the main cause of these events, which have consequences for power utilities and consumers. The minimum requirements of transmission lines performance are regulated and monitored by ANEEL (National Electric Energy Agency) and proposed, through network procedures, by the ONS (National System Operator). This work aims to evaluate a set of alternatives to improve the lightning performance of transmission lines due to direct lightning strikes and to determine some standards for the application of these conventional and unconventional alternatives. Among the existing techniques, the increase in counterpoise wires, the installation of surge arresters and underbuilt wires were used. The technical analysis of this work was based on computer simulations using ATP software, which obtained the resulting overvoltages across insulator string of 230 kV and 500 kV transmission lines, varying the tower-footing grounding impedance from 10 Ω to 80 Ω. The integration method (Disruptive Effect (DE)) was also used to evaluate the occurrence of backflashover. The installation of TL surge arresters provided a reduction of occurrence of backflashover up to 83% and 99% for the 230 kV and 500 kV transmission lines, respectively. An in-depth case study made it possible to identify the ideal value of tower footing grounding impedance to achieve optimal lightning performance of transmission lines. In addition, scenarios with high soil resistivity were evaluated to determine the appropriate length of the counterpoise wires, using or not the alternatives to improve the lightning performance of transmission lines.